INFLUENCE OF TALENT ATTRACTION ON EMPLOYEE RETENTION IN TRANSPORTATION COMPANIES IN ANAMBRA STATE, NIGERIA - Mikella, Nebolisa Chinwe; Oritsejubemi, Akra Victoria (Universitas Negeri Malang, 2024)
Talent attraction and employee retention are important for the success of transportation companies, particularly in Anambra State, Nigeria. This study aimed to identify key aspects influencing talent attraction and retention, and to examine the correlation between these factors. This study used a descriptive correlational research design. The sample comprised of 110 employees selected via stratified random sampling from a population of approximately 1,500 workers from selected transportation companies in Anambra State. Data was collected using a structured questionnaire, validated by experts, and found reliable with a Cronbach’s alpha of 0.85. Descriptive and inferential statistics, including Pearson’s correlation and bootstrap methods, were used for data analysis. Descriptive statistics revealed that competitive salary packages (mean = 1.69), work-life balance initiatives (mean = 3.40), and career growth opportunities (mean = 2.98) were key aspects of talent attraction. Similarly, employee retention was significantly influenced by factors such as job satisfaction (mean = 3.34), adequate compensation packages (mean = 3.30), and positive work environment (mean = 3.35). The correlation analysis showed a moderate positive relationship between talent attraction and employee retention (Pearson correlation = 0.579, p < 0.01). This finding indicates that companies that successfully attract talent are more likely to retain employees over the long term. The results suggested that transportation companies in Anambra State should focus on enhancing both talent attraction and retention strategies to improve organizational performance and reduce turnover. Future research could further investigate the role of leadership and organizational culture in enhancing retention within this industry.